Infrared Radiation Assisted Stokes' Law Based Synthesis and Optical Characterization of ZnS Nanoparticles. (21st February 2016) - Singh, Beer Pal; Upadhyay, Ravish Kumar; Kumar, Rakesh; Yadav, Kamna; Areizaga-Martinez, Hector I.
Abstract : The strategy and technique exploited in the synthesis of nanostructure materials have an explicit effect on the nucleation, growth, and properties of product materials. Nanoparticles of zinc sulfide (ZnS) have been synthesized by new infrared radiation (IR) assisted and Stokes' law based controlled bottom-up approach without using any capping agent and stirring. IR has been used for heating the reaction surface designed in accordance with the well-known Stokes law for a free body falling in a quiescent fluid for the synthesis of ZnS nanoparticles. The desired concentration of aqueous solutions of zinc nitrate (Zn(NO3 )2 ·4H2 O) and thioacetamide (CH3 CSNH2 ) was reacted in a controlled manner by IR radiation heating at the reaction area (top layer of reactants solution) of the solution which results in the formation of ZnS nanoparticles at ambient conditions following Stokes' law for a free body falling in a quiescent fluid. The phase, crystal structure, and particle size of as-synthesized nanoparticles were studied by X-ray diffraction (XRD). The optical properties of as-synthesized ZnS nanoparticles were studied by means of optical absorption spectroscopic measurements. The optical energy band gap and the nature of transition have been studied using the well-known Tauc relation with the help of absorption spectra of as-synthesized ZnS nanoparticles.